The growth implications of Agglomeration in South Africa, 1996-2010 - Msulwa, Rehema (University of Cape Town, 2015)
Includes abstract. === Includes bibliographical references. === The paper investigates whether the spatial distribution of economic activity in South Africa is static or evolving. Testing Gibrat’s Law to determine this, results suggest growth patterns in South Africa have been divergent over the period 1996-2010. The share of population, employment and GVA in the largest municipalities has been increasing relative to the shares in smaller municipalities.